PENGARUH ORGANISASI PEMBELAJAR DAN INOVASI TERHADAP PENINGKATAN KINERJA UKM DI KOTA BOGOR - Manuel Leonard Sirait; Anggraini Sukmawati; I Made Sumertajaya (Jurnal Manajemen., 2015)
The lack of human resources is one of the problem that small and medium enterprises (SMEs) has faced. Human resources in SMEs dont have sufficient knowledge and information and it effects the performances of SMEs. Dealing with people of ASEAN Economic Community will effect the resistance of SMEs in Bogor, due to the competitive and making an increase in quality of human resources towards SMEs in Bogor. This research was to analyze the effect of the learning organization and innovation towards performance of SMEs in Bogor. This research was conducted in Bogor with 46 samples for SMEs and 149 for respondent samples. The technique of sampling was conducted by using multi stage sampling namely the combination of stratified random sampling and proportional sampling. The tabulation data was analyzed by Structural Equation Modelling (SEM) by approaching of Partial Least Square (PLS). The result of this research were (1) the existence of significant influence between learning organization toward innovation, (2) the learning organization gives a significant effect towards the performance of SMEs, (3) innovation gives a significant effect towards the performance of SMEs in Bogor.